Impacts of climate change on economic activities of Vietnamese North Central provinces residents - Lê, Thanh Tú (Trường đại học khoa học xã hội và nhân văn, 2023)
Analysis results of a number of sources of documents by qualitative and quantitative methods not only helps the paper explore the multidimensional impacts of climate change on North Central Vietnam's inhabitants over the past few years, but also confirm that Vietnam's North Central region currently possesses a lot of valuable natural resources and favorable natural conditions to integrate into the national economy in the coming time. In addition to a system of stunning beaches, valuable historical sites, a number of iconic world cultural heritages, quintessential scenic landscapes, unique cultural festivals, and a variety of outstanding cultural traditions, Vietnam's North Central provinces are located in a nationally strategic geographic position, possess a system of internationally important seaports, and are home to most coastal economic zones of the whole country (11 out of 17). However, economic activities of North Central Vietnam's residents have recently been significantly affected by unusual developments of global climate change. While sea level rise has resulted in the increasing inundation of salt water in the nearly the entire region, global warming has made a wide range of cultivated areas more serious fallow and unusual phenomena of natural disasters have made the increasing desertification more alarming than ever. However, the most negatively affected is objectively the economic activities of coastal residents and socially the livelihoods of vulnerable groups such as women, children, and the elderly in underdeveloped areas. In such a situation, it is important to raise people's awareness and understanding of the negative impacts of climate change on their own economic life, but responding efforts of the whole government system plays a decisive role in the entire process of safe adaptation to similar unexpected challenges in the near future.